Evaluasi Program Pendidikan dan Pelatihan Menggunakan Model Kirkpatrick Pada Institusi Pemerintah di Indonesia - Eny Engriyani; Rugaiyah Rugaiyah (Peneliti.net, 2022)
Evaluation of education and training is a series of systems as a whole to see the effectiveness and efficiency of a program and aims to determine program achievements in the short and long term. The aim of this study is to make a systematic review from the previous relevant researches that use the KirkPatrick model evaluation in education and training program activities in government institutions of the Republic of Indonesia between 2016 and 2021. The research method is carried out by studying literature through searching articles and accredited scientific journals. Literature data was examined from various components of the process development on the education and training programs on the KirkPatrick model, namely level 1 reaction, level 2 learning, level 3 behaviour and level 4 impact. The findings of this study show that the evaluation of education and training using the KirkPatrick model carried out in government institutions can enrich the repertoire of practical knowledge with evaluation purposes so that it can eventually be useful as a reference for improving the quality of education and training for further decision and policy making.